Evaluation of Drug Use and its Risks among Young Girls and Unmarried Women in Akwa Ibom State, Nigeria - Effiong, Ben, Victor (American Journal of Social Sciences and Humanities, 2019)
The use of drug by most girls and women with pregnancy is to terminate such pregnancy without concern about its risk. This study surveyed the risk of drug use among 300 respondents, comprising young girls and unmarried women that were randomly selected using a multistage sampling technique from six Local Government Areas in Akwa Ibom State. Data were collected from the respondents with the use of questionnaire and interview. The data were discussed both descriptively and analytically. Findings show an increasingly high rate of drug use to terminate unexpected and unwanted pregnancy despite the availability of facilities that can effect safe abortion and the prevalence of modern contraception. It also shows that the drug users risk damage of their womb in the process. While the unmarried women in the 30-49 age group have withdrawn patronage of drug and substance use to terminate unexpected and unwanted pregnancy, majority of the young girls (15-29 years of age) still prefer the use of drug especially when such factors as not living with biological parents; and pressure from mother, sister, girlfriend, and boyfriend who would not accept responsibility of the pregnancy are considered. These factors also show significant effects in the test of the regression coefficient. The study suggests among others the intensification of campaign on sexual education among the vulnerable population to help check the menace.